Potential implications of thyroid autoantibodies in children, adolescents, and young adults with thyroid nodules in Japan: The Fukushima Health Management Survey - Rina Tazaki; Yurie Kobashi; Nana Nakahata; Mahiro Asano; Norikazu Abe; Haruka Ejiri; Ayako Sato; Natsuki Nagamine; Chisato Takahashi; Yukie Yamaya; Manabu Iwadate; Takashi Matsuzuka; et al. (Endocrine Journal)
There have been no systematic epidemiological evaluations of the relationship between thyroid autoimmunity and the clinical background of young patients with thyroid nodules. We aimed to clarify the clinical features associated with thyroglobulin or thyroperoxidase antibodies (thyroid autoantibodies [Tabs]) in children and young adults with nodules. We performed a cross-sectional study using data from 3,018 participants of 3–29 years of age with nodules, including thyroid cancer, from the Fukushima Health Management Survey. After stratification of the data for body mass index (BMI) and the bilateral width and thickness of the area (BWTAR) as indicators of thyroid volume for age, sex, body surface area (BSA), and sex-adjusted standard deviation score (SDS), trend analyses were performed. A logistic regression analysis was performed using tab-positivity as an objective variable. The overall prevalence of tab-positivity is 13.9%. It was high in females (17%), participants with diffuse goiter (DG) (19.2%), and those with papillary thyroid carcinoma (PTC) (12.8%). The age- and sex-adjusted odds ratios (95% confidence intervals) for BMI-SDS, BWTAR-SDS, presence of DG, diagnosis of PTC, and TSH concentrations were 0.962 (0.863–1.073), 1.263 (1.171–1.361), 7.357 (4.816–11.239), 2.787 (1.965–4.014), and 1.403 (1.257–1.564), respectively. Tab positivity was independently associated with a large thyroid, the presence of DG, the presence of PTC, and a high TSH concentration in patients with nodules. Based on the systematic epidemiologic evidence shown in young patients, Tab positivity might complement ultrasonography for the assessment of the thyroid function and identification of malignancy in younger patients with asymptomatic thyroid nodules.